2016
DOI: 10.1016/j.xphs.2016.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly of Cyclodextrins and Their Complexes in Aqueous Solutions

Abstract: Cyclodextrins (CDs) are enabling pharmaceutical excipients that can be found in numerous pharmaceutical products worldwide. Because of their favorable toxicologic profiles, CDs are often used in toxicologic and phase I assessments of new drug candidates. However, at relatively high concentrations, CDs can spontaneously self-assemble to form visible microparticles in aqueous mediums and formation of such visible particles may cause product rejections. Formation of subvisible CD aggregates are also known to affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 121 publications
(64 citation statements)
references
References 204 publications
(236 reference statements)
0
57
0
Order By: Relevance
“…In CD solutions, dynamic light scattering (DLS) [31,32] and transmission electron microscopy (TEM) [32] have provided reliable evidence of the aggregation phenomenon. The latter has been recognized by several research groups that identified aggregates of different shapes, including spherical and elongated particles, welded fibers, and rods [1,2,19,29].…”
Section: Cyclodextrin -A Versatile Ingredient 46mentioning
confidence: 99%
See 4 more Smart Citations
“…In CD solutions, dynamic light scattering (DLS) [31,32] and transmission electron microscopy (TEM) [32] have provided reliable evidence of the aggregation phenomenon. The latter has been recognized by several research groups that identified aggregates of different shapes, including spherical and elongated particles, welded fibers, and rods [1,2,19,29].…”
Section: Cyclodextrin -A Versatile Ingredient 46mentioning
confidence: 99%
“…[2,3,30]). However, the mechanisms of CD aggregation and CD complex aggregation have not yet been fully understood.…”
Section: Cyclodextrin -A Versatile Ingredient 46mentioning
confidence: 99%
See 3 more Smart Citations